2017
DOI: 10.1590/abd1806-4841.20175140
|View full text |Cite
|
Sign up to set email alerts
|

Particular characteristics of atopic eczema in tropical environments. The Tropical Environment Control for Chronic Eczema and Molecular Assessment (TECCEMA) cohort study

Abstract: BackgroundAtopic dermatitis is a prevalent health problem in the world. Allergic sensitization is an important risk factor, but the roles of other factors, inherent in tropic region, are unknown.ObjectiveA cohort study was designed in a tropical city to investigate molecular and environmental risk factors for eczema, considering as particular features perennial exposure to mites, poor living conditions and others tropical characteristics.Methods433 patients were included at baseline and biological samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…The creation of a prognostic model evaluating the magnitude of each individual factor could be useful. 41 Explanation. Most childhood dermatitis remitted before puberty, nevertheless, from 1% to 25% of patients persist with symptoms even in adulthood.…”
Section: Can Atopic Dermatitis Be Prevented?mentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of a prognostic model evaluating the magnitude of each individual factor could be useful. 41 Explanation. Most childhood dermatitis remitted before puberty, nevertheless, from 1% to 25% of patients persist with symptoms even in adulthood.…”
Section: Can Atopic Dermatitis Be Prevented?mentioning
confidence: 99%
“…Most childhood dermatitis remitted before puberty, nevertheless, from 1% to 25% of patients persist with symptoms even in adulthood. 20,41 Findings from 14 systematic reviews published before 2016 observed that persistent atopic dermatitis is associated with more severe disease at the time of diagnosis, onset after the age of two years and being a female. 42 A systematic review in- cluding 45 studies was considered and found that a later onset increased persistence.…”
Section: Can Atopic Dermatitis Be Prevented?mentioning
confidence: 99%
“…Нередко у детей атопический дер-матит, начавшийся в младенческом возрасте, может пе-рерасти в «аллергический марш» -пищевую аллергию, вслед за которой формируется аллергический ринит, аллергический конъюнктивит и другие аллергические заболевания [7,8]. В свою очередь, аллергические забо-левания существенно снижают качество жизни ребенка и способствуют физической и эмоциональной дезадап-тации как пациента, так и членов его семьи [9]. В свя-зи с вышесказанным особую актуальность приобретает проблема профилактики и лечения аллергической пато-логии.…”
Section: Issn 1816-5095 (Print); Issn 2500-0845 (Online) Doi: 101800unclassified
“…Кроме того, теория влияния ги-гиены («en:hygiene hypothesis»), выдвинутая в 1989 году David P. Strachan, утверждает, что переход к соблюдению норм гигиены предотвращает контакт организма со мно-гими антигенами, что вызывает недостаточную загрузку иммунной системы (особенно у детей). Это связанно с тем, что наш организм должен постоянно противосто-ять определённому уровню внешних угроз, при отсут-ствии которых иммунная система начинает реагировать на антигены, не являющиеся аллергенами [9][10][11]. Кроме того, исследования последних лет свидетельствуют о не-оправданном использовании антибиотиков, что приво-дит к увеличению числа пациентов, страдающих аллер-гическими реакциями [12,13].…”
Section: Issn 1816-5095 (Print); Issn 2500-0845 (Online) Doi: 101800unclassified
See 1 more Smart Citation